2020
DOI: 10.1177/0300060520962910
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contractility modulation attenuates structural and electrical remodeling in a chronic heart failure rabbit model

Abstract: Background Cardiac contractility modulation (CCM) is non-excitatory electrical stimulation for improving cardiac function. This study aimed to evaluate the effects of CCM on structural and electrical remodeling in a rabbit model of chronic heart failure (CHF). Methods Thirty rabbits were randomly divided into the sham, CHF, and CCM groups. The CHF model was induced 12 weeks after trans-aortic constriction by pressure unloading and CCM was delivered to the myocardium for 4 weeks. Corrected QT intervals, the ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…These changes in ion channel proteins are similar to those in other disease states. Kv4.3 proteins have been verified to be downregulated in failing hearts (38,42), while the expression levels of Kv4.2 and KChIP2 proteins decreased in the myocardial tissues of type 2 diabetic rats compared with nondiabetic controls (43). BB536, a bifidobacterium longum strain, was then used to treat CKD rats; we found that BB536 could reduce IS levels in serum and heart tissue of CKD rats, and it reversed the decreased Kv4.2, Kv4.3, and KChIP2 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in ion channel proteins are similar to those in other disease states. Kv4.3 proteins have been verified to be downregulated in failing hearts (38,42), while the expression levels of Kv4.2 and KChIP2 proteins decreased in the myocardial tissues of type 2 diabetic rats compared with nondiabetic controls (43). BB536, a bifidobacterium longum strain, was then used to treat CKD rats; we found that BB536 could reduce IS levels in serum and heart tissue of CKD rats, and it reversed the decreased Kv4.2, Kv4.3, and KChIP2 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge the effects of CCM stimulation on human QT interval remains unknown. However, one publication demonstrated CCM‐induced attenuation of prolonged QTc interval in a rabbit HF model in vivo (Ning et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a canine HFrEF model, CCM therapy reduced left ventricular filling pressure due to the improvement of ventricular compliance and relaxation and improved diastolic Ca ++ physiology [ 29 ]. In a rabbit HFrEF model, CCM therapy reduced cardiac expression of connective tissue growth factor and galectin-3 (a pro-fibrotic marker involved in myocardial structural remodeling) with a reduction of myocardial fibrosis [ 11 ]. These effects of CCM therapy observed in animal models may explain the improvement in diastolic function and GLS observed in this study, as well as a reduction of the E/e’ ratio and of the NT-proBNP plasma levels both expression of left ventricular filling pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the gold standard for quantification of MEE is cardiac catheterization (bilateral and of the coronary sinus) [ 3 ], recently, an echocardiographic approach has been proposed, enabling more extensive clinical applications [ 4 , 5 ]. Cardiac contractility modulation (CCM) is an innovative therapy for the treatment of patients with HF [ 6 ] that through delivery, via an implantable device (Optimizer Smart ® , Impulse Dynamics, Marlton, NJ, USA), of high-energy biphasic non-excitatory impulses during the absolute refractory period of the cardiomyocytes results in improved calcium handling [ 7 ], reverses titin downregulation and fetal gene expression [ 8 , 9 ] and reduces adrenergic tone and myocardial fibrosis [ 10 , 11 ]. These effects on failing myocardium biology result in an improvement of quality of life and functional capacity [ 12 ], reduction of hospitalizations [ 13 ], and a biventricular reverse remodeling [ 14 , 15 ] in patients with HFrEF.…”
Section: Introductionmentioning
confidence: 99%